2021
DOI: 10.1122/8.0000138
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven physics-informed constitutive metamodeling of complex fluids: A multifidelity neural network (MFNN) framework

Abstract: In this work, we introduce a comprehensive machine-learning algorithm, namely, a multifidelity neural network (MFNN) architecture for data-driven constitutive metamodeling of complex fluids. The physics-based neural networks developed here are informed by the underlying rheological constitutive models through the synthetic generation of low-fidelity model-based data points. The performance of these rheologically informed algorithms is thoroughly investigated and compared against classical deep neural networks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 84 publications
1
25
0
Order By: Relevance
“…Studies have demonstrated that ML methods can classify conformations of polymer chains and characterize structural relaxations in glassy materials [37,49,50]. However, with the exception of a few recent developments [51], there is a lack of utilization of ML techniques in examining the rheological behavior of liquids. The application of ML methods in the specific context of NEMD simulations related to tribological applications has not been explored to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that ML methods can classify conformations of polymer chains and characterize structural relaxations in glassy materials [37,49,50]. However, with the exception of a few recent developments [51], there is a lack of utilization of ML techniques in examining the rheological behavior of liquids. The application of ML methods in the specific context of NEMD simulations related to tribological applications has not been explored to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…With an ever-increasing computational power and the ability to process large data sets, data-driven models have become indisputable and powerful tools. With a limited number of studies utilizing ML algorithms 33 – 36 , the field of soft matter and more specifically rheology is lagging behind in leveraging such advanced methodologies. This is partially due to the ambiguous consequences of the produced meta-models and their adherence to the fundamental underlying physics.…”
Section: Introductionmentioning
confidence: 99%
“…In the case with unknown governing laws, the pathway to embedding the physical laws into the training process has to change accordingly. One such method would be to introduce the physical intuition to the NN implicitly and by means of physics-based synthetic data, generated from constitutive laws 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Of these fields this work is primarily interested in the development and use of PINNs [28,29,30,31,32,33,34,26,35,36,37,38,39]. The approach in PINNs is to use as an input-output pair to the neural network a fundamental variable, or set of variables for the physical problem, and use these variables to construct the quantities that appear in the governing equation of motion, such as the velocity and pressure fields in a fluids problem.…”
Section: Introductionmentioning
confidence: 99%